Evaluation of long-term stability of bilateral sagittal split osteotomy in individuals with different growth patterns - Tojan Chacko; Jose Jacob; Midhun Raghav; Supriya Gopalakrishnan; Anuradha Parayancode; Vineetha V Menon (Journal of Pharmacy and Bioallied Sciences, 2020)
Objective: Bilateral sagittal split osteotomy (BSSO) is a routinely used surgical step for the correction of a class III with mandibular prognathism. Many factors influence the stability of the surgical correction achieved. This study was designed to access the role of growth pattern in the surgical stability after a BSSO correction. Materials and Methods: A total of 18 individuals (6 vertical growers, 6 horizontal growers, and 6 normal growing individuals) were considered for the study. Five parameters, horizontal plane (HP)–pogonion (POG) angle, HP-occlusal plane angle, POG height, POG depth, and Point B depth, were measured and compared postsurgically and in the follow-up phase. Result: Vertical growing individuals showed greater tendency for relapse and clockwise rotation of mandible postsurgically. No major difference was observed in the normal and horizontal growing individuals. When planning BSSO on vertical growing patient, utmost care should be taken to prevent posttreatment relapse to ensure better surgical stability.